2018
DOI: 10.1039/c8ra02212g
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic degradation of ethylene by Ga2O3 polymorphs

Abstract: In this work, we fabricated four different Ga2O3 polymorphs, namely, α-, β-, γ-, δ-Ga2O3, and investigated their photocatalytic activities by the degradation of ethylene under ultraviolet (UV) light irradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The band gap and valence band position of the nanowires were further determined to be 4.21 and 3.49 eV, respectively, on the basis of both UV–vis absorption and XPS valence spectra (Figure S36). , For sustainability investigation, the catalyst was also examined for its anti-photocorrosion properties. There was no noticeable decrease in the degradation efficiency during four successive cycles (Figure d), demonstrating excellent photostability and reusability of the material.…”
Section: Resultsmentioning
confidence: 99%
“…The band gap and valence band position of the nanowires were further determined to be 4.21 and 3.49 eV, respectively, on the basis of both UV–vis absorption and XPS valence spectra (Figure S36). , For sustainability investigation, the catalyst was also examined for its anti-photocorrosion properties. There was no noticeable decrease in the degradation efficiency during four successive cycles (Figure d), demonstrating excellent photostability and reusability of the material.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover the observed peaks did not match with the XRD peaks of polymorphs of Ga 2 O 3 (α-, γ-, δ-, ε-) other than β-phase. 26,27 The peak (400) with highest intensity was used to determine the average crystallites size (D) of the samples. To determine D, Debye-Scherrer formula (given below) was used:…”
Section: Resultsmentioning
confidence: 99%
“…Apart from TiO 2 , some semiconductors (such as Bi 2 WO 6 , gallium trioxide) are also used to degrade ethylene. 50 Unlike TiO 2 , Bi 2 WO 6 can use visible light with a wavelength of 420-460 nm for photocatalytic degradation. 51,52 Xie et al 52 used the casting method to prepare graphene oxide/Bi 2 WO 6 /starch film and found that the film has good photocatalytic degradation performance under visible light and good recyclability.…”
Section: Packaging Using Photocatalytic Technologymentioning
confidence: 99%
“…Apart from TiO 2 , some semiconductors (such as Bi 2 WO 6 , gallium trioxide) are also used to degrade ethylene 50 . Unlike TiO 2 , Bi 2 WO 6 can use visible light with a wavelength of 420–460 nm for photocatalytic degradation 51,52 .…”
Section: Different Types Of Erpmentioning
confidence: 99%